Recovery and functional outcome after radial nerve palsy in adults with a humeral shaft fracture: a multicenter prospective case series - Saskia H. Van Bergen, BSc; Esther M.M. Van Lieshout, PhD, MSc; Michael H.J. Verhofstad, MD, PhD; Dennis Den Hartog, MD, PhD; Ivo Beetz, MD, PhD; Hugo W. Bolhuis, MD; P. Koen Bos, MD, PhD; Maarten W.G.A. Bronkhorst, MD, PhD; Milko M.M. Bruijninckx, MD; Jeroen De Haan, MD, PhD; Axel R. Deenik, MD, PhD; P. Ted Den Hoed, MD, PhD; et al. (JSES International, 2023)
Background: The consequences of radial nerve palsy associated with a humeral shaft fracture are unclear. The aim of this study was to examine the functional recovery of radial nerve palsy, at presentation or postoperatively, in patients with a humeral shaft fracture. Methods: Data from patients who participated in the HUMeral shaft fractures: measuring recovery after operative versus non-operative treatment (HUMMER) study, a multicenter prospective cohort study including adults with a closed humeral shaft fracture Arbeitsgemeinschaft für Osteosynthesefragen (AO) type 12A or 12B, and had radial nerve palsy at presentation or postoperatively, were extracted from the HUMMER database. The primary outcome measure was clinically assessed recovery of motor function of the radial nerve. Secondary outcomes consisted of treatment, functional outcome (Disabilities of the Arm, Shoulder, and Hand and Constant–Murley Score), pain level, quality of life (Short Form-36 and EuroQoL-5D-3L), activity resumption, and range of motion of the shoulder and elbow joint at 12 months after trauma. Results: Three of the 145 nonoperatively treated patients had radial nerve palsy at presentation. One recovered spontaneously and 1 after osteosynthesis. Despite multiple surgical interventions, the third patient had no recovery after entrapment between fracture fragments. Thirteen of the 245 operatively treated patients had radial nerve palsy at presentation; all recovered. Nine other patients had postoperative radial nerve palsy; 8 recovered. One had ongoing recovery at the last follow-up, after nerve release and suture repair due to entrapment under the plate. At 12 months, the functional outcome scores of all patients suggested full recovery regarding functional outcome, pain, quality of life, activity resumption, and range of motion. Conclusion: Radial nerve palsy in patients with a humeral shaft fracture at presentation or postoperatively functionally recovers in 94% and 89%, respectively.